Diagnostic Accuracy of the Ambulatory EEG vs. Routine EEG for First Single Unprovoked Seizures and Seizure Recurrence: The DX-Seizure Study - Hernández-Ronquillo, Lizbeth; Thorpe, Lilian; Dash, Dianne; Hussein, Tabrez; Hunter, Gary; Waterhouse, Karen; Laboni Roy, Pragma; Téllez-Zenteno, Jose F. (Frontiers in Neurology, 2020)
Rationale: The DX-Seizure study aims to evaluate the diagnostic accuracy (sensitivity, specificity, positive predictive value, negative predictive value, and likelihood ratio) of the ambulatory EEG in comparison with the first routine EEG, and a second routine EEG right before the ambulatory EEG, on adult patients with first single unprovoked seizure and define the utility of ambulatory EEG in forecasting seizure recurrence in these patients after one-year follow-up. Methods: The DX-Seizure study is a prospective cohort of 113 adult patients (>18-year-old) presenting with first unprovoked seizure to the Single Seizure Clinic for evaluation. These patients will be assessed by a neurologist/epileptologist with the first routine EEG (referral EEG) and undergo a second routine EEG and ambulatory EEG. The three EEG (first routine EEG as a gold standard) will be compared and evaluated their diagnostic accuracy (sensitivity, specificity, positive predictive value, negative predictive value, and likelihood ratios) with respect to epileptiform activity and other abnormalities. One-year follow-up of each patient will be used to assess the recurrence of seizures after a first unprovoked seizure and the utility of the ambulatory EEG to forecast these recurrences. Expected Results: We await Ambulatory EEG to increase the accuracy to detect spike-wave/seizures abnormalities to improve timely and accurate diagnosis of epilepsy in patients with single unprovoked seizures.